The Pathogenesis of Extraintestinal Manifestations: Implications for IBD Research, Diagnosis, and Therapy. (15th November 2018) - Hedin, C R H; Vavricka, S R; Stagg, A J; Schoepfer, A; Raine, T; Puig, L; Pleyer, U; Navarini, A; van der Meulen-de Jong, A E; Maul, J; Katsanos, K; Kagramanova, A; et al.
Abstract: This article reports on the sixth scientific workshop of the European Crohn's and Colitis Organisation [ECCO] on the pathogenesis of extraintestinal manifestations [EIMs] in inflammatory bowel disease [IBD]. This paper has been drafted by 15 ECCO members and 6 external experts [in rheumatology, dermatology, ophthalmology, and immunology] from 10 European countries and the USA. Within the workshop, contributors formed subgroups to address specific areas. Following a comprehensive literature search, the supporting text was finalized under the leadership of the heads of the working groups before being integrated by the group consensus leaders.